Improved access to research data in the field of vocational education and training : BIBB's Research Data Centre - Alda, Holger [Verfasser] (My University, 2011)
"BIBB launched a Research Data Centre (BIBB-FDZ) in 2008. The FDZ processes the microdata from BIBB research projects and makes the respective data sets available to external researchers and scholars for their own analysis. As a constitutive part of the German Data Infrastructure coordinated by the German Data Forum (RatSWD), BIBB-FDZ helps to reduce the workload and costs involved in conducting data surveys in the field of vocational education and training (VET) by assisting external researchers in the use of existing data." (Autorenreferat, BIBB-Doku)
Keywords: S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); T 3 Forschungsmethoden; Forschungsdatenzentrum; Berufsbildungsforschung; Datendokumentation